Urgensi Pembentukan Peraturan Daerah tentang Perlindungan dan Pengelolaan Hutan Perempuan Teluk Youtefa Kota Jayapura, Papua - Ilham, Ilham; Idris, Usman; Kadir, Akhmad; Tokang, Maspawati; Patmasari, Eka (Program Doktor Ilmu Sosial Universitas Cenderawasih, 2023)
This article discusses the urgency of establishing local regulations on the protection and management of women's forests based on traditional wisdom. The type of research used is qualitative with a library approach. Data were obtained from various literature sources relevant to the research topic. Data analysis was carried out through three stages; data reduction, data presentation and verification. Furthermore, the validity of the data was tested using triangulation and discussion techniques. The results of this study show that the mangrove forest area of Youtefa Bay based on customary law principles belongs to women in the local language called